(3dHGH GdJChjd aj eYGde GdJfRjds - (3YdGA GdOjf Ydj Hf eMeO GdNGRf GdHZOGOj, GdNGRf,J (B741 (3g` s
(3ChdgG (B:s
(3ShQI GdJhHI hgj eOfjI HELeGYge bGd GHf GdLhRi Shi BjJjf ai BNQgG s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI GdaQbGf hBNQ GdehLhO efg(B: ((3aSha jchf dRGeG(B) (3gPG JgOjO dge Cf jcchf JcPjHge dRGeG hGdeYfi jchf GdJcPjH dGReG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B156s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1540s
Keywords: (3GdJaSjQ hYdhe GdbQBfs